PELAKSANAAN PEMBELAJARAN TEMATIK DI SDN 1 KRAGILAN - Sakti, Bayu Purbha; Budiyono, Sri (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
The purpose of this study  is to describe the implementation of thematic learning in SD N 1 Kragilan. The research approach used is qualitative. The author determines SDN 1 Kragilan as a research location. Research data were collected by observation and interview techniques. Data analysis techniques used include the phase of data reduction, data display, and data verification. The results showed that the teachers were able to understand thematic learning. Thematic learning is learning taught to children that combines several subjects put together in a theme. Thematic learning can take lessons from the natural surroundings and everyday life. The teachers have obstacles in carrying out thematic learning. The teachers find it difficult to run a thematic learning assessment system. Students are not yet accustomed to using thematic learning. The teachers already have a solution in thematic learning. The teachers exchange information, knowledge, and opinions with other teachers about thematic learning.